Eccentrically loaded externally confined HSC columns - Ma, Chow Khun (2013)
The application of steel-straps confinement has been proven to be effective in increasing the strength and ductility of High-Strength Concrete (HSC) column comparable to Fiber-Reinforced Polymer. However, most of the research of confined HSC column has mainly concentrated on concentric loading. In actual practical condition, most of the columns are subjected to eccentric loading. The scarcity of the experimental data for eccentric loaded confined HSC column has prevented the potential use of this type of structure element. In this paper, five short HSC columns were tested. The specimens were confined with steel-straps and tested with 25mm and 50 mm eccentric loading. The results show that steel-straps confinement increases the strength and deformability of high-strength concrete column, although the confinement effects in eccentrically loaded columns are not as pronounces as concentrically loaded column.